2013
DOI: 10.1002/pd.4281
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of obstetrical risk using maternal serum markers and clinical risk factors

Abstract: While detection rates are low, the combination of maternal serum markers and obstetrical history helps to identify a small subset of women at higher risk for serious perinatal events and severe pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
2
14
0
1
Order By: Relevance
“…Metcalfe et al (7) reported that biomarkers currently used to screen for aneuploidy have detection rates too low to identify women at risk for adverse obstetrical outcomes. Menon et al (36) reviewed 116 different biomarkers assayed 578 times in 217 studies, and found that no single biomarker could reliably predict PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Metcalfe et al (7) reported that biomarkers currently used to screen for aneuploidy have detection rates too low to identify women at risk for adverse obstetrical outcomes. Menon et al (36) reviewed 116 different biomarkers assayed 578 times in 217 studies, and found that no single biomarker could reliably predict PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Although several prediction models for PE have been reported to date, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] they require data from examinations (blood test and/or Doppler velocimetry) and complex questionnaires on maternal background. The present study was conducted in order to determine predictive risk factors for GH and PE in Japan, develop a nomogram for calculating estimated risk ratios of GH and PE, and identify high-risk women in prenatal visits.…”
Section: Introductionmentioning
confidence: 99%
“…race and obesity) and blood pressure. The list of such markers includes pregnancy associated plasma protein A, placental growth factor, placental protein‐13, and ADAM‐12 . Studies published in 2013 have validated the predictive ability of such markers identified in previous small‐scale discovery studies.…”
Section: The Use Of Serum Analytes To Determine Fetal Well‐beingmentioning
confidence: 99%